Desain Elektroda Selektif Ion Untuk Logam Timbal (II) (ESI-Pb (II)) Menggunakan Ionofor p-t-Butilkaliks [4] Arena - IP, Awaluddin; Wahab, Abd. Wahid; Maming, Maming (Al-Kimia, 2015)
This study aims to determine the design pattern ESI-Pb (II) with ionophores pt-butilkaliks [4] arena. In this study, ion selective electrode is designed for the determination of lead (II) (ESI-Pb (II)) using ionophores pt-butilkaliks [4] arenas and diimmobilasi on a matrix of polyvinyl chloride (PVC) in the membrane ESI-Pb (II). The results showed a design pattern ESI-Pb (II) with ionophores pt-butilKaliks [4] arena is best to ESI with membrane composition (% by weight), namely: (pt-butilKaliks [4] arena: KTCPB: DOS: PVC) is 3 : 2: 60: 35 with the Nernst factor: 27.61 mV / decade